UN-water global annual assessment of sanitation and drinking-water GLAAS 2010 : targeting resources for better results - World Health Organization; UN-Water (Geneva, Switzerland : World Health Organization, 2010)
This report contains a large number of data and analyses on sanitation and drinkingwater, making it a resource that can be used to strengthen policies and assist decision-makers.
Title from pdf t.p. viewed (July 6, 2010).
Keywords: Drinking water -- International cooperation -- Evaluation; Water quality -- International cooperation -- Evaluation; Water quality management -- International cooperation -- Evaluation; Sanitation -- International cooperation -- Evaluation; Water-supply -- International cooperation -- Evaluation